Study of sound absorption using acoustic impedance tube - Tan, Darrell Jun Guo (2018)
Sound absorption has always been an important consideration in infrastructure design for the selection of suitable materials for enforcing noise control in places such as libraries, industrial locations, and homes. However, proper noise control methods can be costly to build and maintain in people's homes. This project seeks to explore a more affordable means of improving the sound absorption properties of the walls for office and residential places. In this project, eight sample discs made of Ceramix were casted and their sound absorption coefficients were measured using the Two-Microphone Impedance Measurement Tube Type 4206. The sample discs were then coated with a layer of water and oil-based paints of differing titanium oxide contents and the sound absorptions were measured again. The measurements were repeated after second layers of paint were applied to each disc. The experiment was conducted twice, once in the absence of air cavity and the other with a 10mm air cavity at the back of each disc.